PENGGUNAAN TEKNIK STORY MAPPING DALAM MEMAHAMI TEKS NARATIF PADA SISWA KELAS X KC DI SMKN3 KOTA BENGKULU - Minha, Yulita (TRIADIK, 2017)
ABSTRACTThis study aimed to describe the process of improving students' reading comprehension ofnarrative text through the story mapping technique at SMK Negeri 3 Bengkulu City. Thisresearch was conducted on a class X student, especially students of class X KC 12018/2019academic year as research subjects. The method used in this research is descriptive qualitativeresearch. Data collection instrument in this study was the observation sheet and a list ofquestions for the interview. The technique for analyzing data is data reduction, data display,and drawing conclusion. The results of this study indicate that the story mapping techniquecan improve students' reading comprehension. The students were able to map the basiccomponents of a story like setting, problems, goals, actions, and results. It can help students inanswering the questions from the text. Story mapping technique provides structure andorganization so that students are able to understand the story more effectively.Keywords: Narrative Text, Story Mapping Technique